The Effect Of Core Stability Exercise (CSE) On Balance In Primary School Students - Lengkana, Anggi Setia; Tangkudung, James; Asmawi, Asmawi (Journal of Education, Health and Sport, 2019)
There are many forms of exercise that can improve the quality of balance, either static or dynamic Core Stability Exercise (CSE) is one of them. Based on the explanation, this research intends to apply various forms of balance training to children who participate in various sports in primary school-age. The purpose of this research is to find out the effectiveness of CSE in supporting good body balance in children. This research employed an experimental research design. The population was the students of a primary school in Sumedang Regency, West Java. Random cluster sampling was used to select 60 primary school students with an average age of 10-11 years as the participants in this research. Moreover, Standing Stork Test – Blind was used as the measuring instrument to obtain objective data. The results showed that CSE significantly affected the balance of primary school students.